Вивчення ефективності зупинки кровотечі за допомогою "СІЧ-Турнікета" - Степанова, Надія Володимирівна; Скоба, В. С.; Мікаєлян, Геннадій Ромеович; Прокопченко, Олександр Євгенович; Потоцька, Олена Іванівна; Stepanova, N. V.; Skoba, V. S.; Mikaelyan, G. R.; Prokopchenko, E. E.; Pototsckaya, O. I. (ЗНУ, 2018)
Статтю присвячено вивченню ефективності зупинки кровотечі за допомогою «CІЧ-Турнікета», який у 90 % випадків надає можливість уникнути тяжких наслідків крововтрати при ураженні кінцівок. Постає питання: «Чи дійсно є доцільним накладання турнікета на 2 години, з 2-3 обертами закрутки турнікета (згідно протоколу), та які зміни будуть виникати в кінцівці нижче турнікета та в організмі в цілому?» Тестування проводились на добровольці при різній кількості обертів закрутки турнікета на певні проміжки часу з контролем суб’єктивних та об’єктивних даних фізіологічними методами обстеження. Отримані результати свідчать про доцільність використання «CІЧ-Турнікета» для зупинки кровотечі, але ж при 3 обертах закрутки турнікета спостерігаються зачні негативні наслідки для травмованої кінцівки і організму загалом. Достатньо проводити 1,5-2 оберти закрутки турнікета для повного припинення кровотечі, але визначення максимально можливого часу фіксації турнікета вимагає поглибленого дослідження і уточнення, що й буде метою подальшої наукової роботи. The subject of this study is an effectiveness of stopping bleeding by «SICH-Tourniquet» use. In the conditions of ATO in Ukraine numerous mortalities of the Armed Forces of Ukraine were attributed to the delayed first aid and it became necessary to study the effectiveness of hemostatic tourniquet use. According to official data on October 28, 2017, the number of casualties for the Armed Forces of Ukraine in the Donbass region was reported at 10,710 people. Experts have proven that out of all mortalities on the battlefield about 90 % of them could be eliminated by simply using a tourniquet to stop bleeding of limbs, restoring airway patency, and a rapid treatment of an intense pneumothorax. About 15-27 % of prehospital casualties could be saved if properly treated, namely, by stopping bleeding. Is it really advisable to apply a tourniquet for a duration of 2 hours with 2-3 revolutions of its handle and what changes will occur in the whole body? The study of an effectiveness of stopping bleeding by «SICH-Tourniquet» use with different number of revolutions of its handle was conducted by controlling some subjective and objective data and other additional methods of observation. The obtained results indicate that a quick application (or use) of «SICH-Tourniquet» stops bleeding. After analyzing the experiment with 1,5 and 2 revolutions of the tourniquet handle we received almost identical data in those series, but there were some differences as well. The differences can be noticed in the heart 71 Вісник Запорізького національного університету № 1, 2018 rate increase at 1,5 revolutions compared with 2 revolutions. The heart rate at 1,5 was measured at 18 beats per minute, while at 2 revolutions the heart rate increased to 22 beats per minute, and at 3 revolutions up to 41 beats per minute, indicating a decreased pressure on the hemodynamic system at 1,5-2 revolutions compared with 3 revolutions. When studying the diameter of arteries the same indicators were observed: all arteries below the tourniquet experienced a lack of blood flow, and above it – a.subclavia = 0,9 at 1,5-2 revolutions, which is smaller than at 3 revolutions (the diameter was 1,1) indicating less change in central hemodynamics. At the same time BM at 1,5 revolutions increased to 19, at 2 revolutions to 20, and at 3 revolutions the pain increased significantly to 24. There was also some indication of a decreased pressure on the respiratory system at 1,5-2 revolutions of the tourniquet handle compared with 3 revolutions. During the experiment subjective sensations were constantly changing: the pain was increasing at 3 revolutions to 10 points; and at 1,5-2 only to 7-8 points which was much easier tolerated by the subject. A rather intense feeling (according to the protocol we used no anesthetics) caused the study to stop on the 30th minute due to a feeling of numbness and a decreased sensitivity close to a complete anesthesia was observed at 3 revolutions; and at 1,5-2 revolutions - the severity of those feelings were significantly lower.
Study of the efficiency of the bleaching stock with «sich-tournicket» assistance
Keywords: ефективність зупинки кровотечі; «СІЧ-Турнікет»; наслідки використання згідно протоколу; фізіологічні показники; an effectiveness of stopping bleeding; «SICH-Tourniquet»; revolutions of the tourniquet